2020
DOI: 10.3390/microorganisms8060831
|View full text |Cite
|
Sign up to set email alerts
|

Novel 2D and 3D Assays to Determine the Activity of Anti-Leishmanial Drugs

Abstract: The discovery of novel anti-leishmanial compounds remains essential as current treatments have known limitations and there are insufficient novel compounds in development. We have investigated three complex and physiologically relevant in vitro assays, including: (i) a media perfusion based cell culture model, (ii) two 3D cell culture models, and (iii) iPSC derived macrophages in place of primary macrophages or cell lines, to determine whether they offer improved approaches to anti-leishmanial drug discovery a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…Macrophages play a pivotal role in pathogen clearance. The fact that iMphs are infectable with various intracellular bacteria (e.g., S. typhimurium , P. aeruginosa , M. tuberculosis ) and viruses (e.g., HIV, ZIKA, and dengue) allows using them as a standardized model to study Mφ-pathogen interactions and to search for key targets to reinforce a Mφ-mediated immune defense ( van Wilgenburg et al, 2013 ; Hale et al, 2015 ; Ackermann et al, 2018 ; Lang et al, 2018 ; Bernard et al, 2020 ; Haake et al, 2020 ; Nenasheva et al, 2020 ; O’Keeffe et al, 2020 ).…”
Section: Imph Applications and Prospectsmentioning
confidence: 99%
“…Macrophages play a pivotal role in pathogen clearance. The fact that iMphs are infectable with various intracellular bacteria (e.g., S. typhimurium , P. aeruginosa , M. tuberculosis ) and viruses (e.g., HIV, ZIKA, and dengue) allows using them as a standardized model to study Mφ-pathogen interactions and to search for key targets to reinforce a Mφ-mediated immune defense ( van Wilgenburg et al, 2013 ; Hale et al, 2015 ; Ackermann et al, 2018 ; Lang et al, 2018 ; Bernard et al, 2020 ; Haake et al, 2020 ; Nenasheva et al, 2020 ; O’Keeffe et al, 2020 ).…”
Section: Imph Applications and Prospectsmentioning
confidence: 99%
“…Modifications to investigate the impact of rate of flow of culture media and different scaffold support for macrophages on drug efficacy showed shifts in EC 50/90 values for amphotericin B and miltefosine in cultures under RSC Medicinal Chemistry Review medium flow. 52,92 Further changes such as the addition of a second medium reservoir introducing fresh medium into the assay design, similar to the hollow fibre infection model, would enable the opportunity to test continuous versus intermittent drug exposure. 93 Recent investigations demonstrate how the hollow fibre infection model can be used to reproduce pharmacokinetic profiles of clinically relevant anti-mycobacterial drug combinations, simulating drug levels at the target lung tissue.…”
Section: New Techniques To Progress Treatments For CLmentioning
confidence: 99%
“…However, this is an in vitro parameter, and like in all antimicrobial studies 51 it has several critical limitations: (i) the set time period and concentration of drug exposure, which is critically different from the transient nature of the in vivo PK exposure in animal models and humans, (ii) the different properties of host cells subject to differences in nutrient supply, O 2 tensions and flow (see ref. 17 for further discussion on impact on Leishmania and 52 for effect of flow on drug activity) and (iii) does not take into account the in vivo survival and division of pathogens which may have fast dividing as well as quiescent populations. 53,54 Hence the determination of the in vivo PD parameter, must determine skin amastigote burden over a dose range using qPCR or other methods.…”
Section: Drug Development Paradigmmentioning
confidence: 99%
“…Over twenty morphologically indistinguishable species of Leishmania cause this disease that is transmitted by the bite of infected female phlebotomine sand flies [ 53 ]. The promastigotes are injected into the host by the fly during blood meals and are engulfed by phagocytic cells, mainly macrophages.…”
Section: Specific Cell Type Generation: Stem Cellsmentioning
confidence: 99%
“…Though the objective of this study was to highlight the necessity for screening for this parasite before stem cell transplantation in endemic countries, it showed that stem cells can be a versatile model to study this parasite [ 60 ]. In a recent study, hiPS-derived macrophages were shown to be much better at supporting infection by L. major and L. amazonensis and very good for L. mexicana , as compared with THP1 and primary macrophages [ 53 ]. Several compounds were tested in this system with a similar outcome, though IPS-derived macrophages displayed the highest effect in some cases.…”
Section: Specific Cell Type Generation: Stem Cellsmentioning
confidence: 99%